Penggunaan Teka-teki Matematika dalam Pembelajaran Trigonometri - Saragih, Rini Meilani; Rahmadani, Tiara; Marjanatun A, Sanniyyah; Surbakti, Vera Kennina Br; Rosmaini, Rosmaini (Papanda, 2024)
This research aims to analyze the impact of using mathematical puzzles in trigonometry learning. The problem faced is the low interest and motivation of students in learning trigonometry as well as the lack of understanding of basic concepts. To address this issue, a descriptive research method with a case study approach was used, involving students from MAS Hidayahtullah Medan as research subjects. Data were collected through interviews, observations, and literature studies. The results of the research indicate that the use of mathematical puzzles significantly increases students' interest and motivation. Mathematical puzzles make learning more enjoyable and challenging, thereby motivating students to better understand trigonometry material. Additionally, mathematical puzzles are also effective in enhancing the understanding of basic trigonometry concepts, as evidenced by students' improved ability to solve trigonometry problems after using this medium. The conclusion of this study shows that mathematical puzzles are an effective learning medium to increase students' interest, motivation, and understanding in trigonometry learning. It is hoped that mathematics teachers can integrate mathematical puzzles into the learning process to create a more engaging and effective learning environment.